Solving the quadratic 0-1 problem - Schutz, G. (2013)
The quadratic 0-1 programming is a discrete optimization problem, with many important applications. Difficult graph problems can be formulated and solved as a quadratic 0-1 programming problem. This is a NP-hard combinatorial problem very difficult to solve, even if the dimension is small. The branch-and-bound algorithms are the most used for solving exactly this sort of problems. In this paper, based on an efficient sequential branch-and-bound algorithm for the unconstrained quadratic 0-1 programming, we study the behaviour of its parallel implementation using transputers and present some computational results. We also analyse the workload distribution among processors.